Diagnóstico parcial de las necesidades y fortalezas en la gestión metrológica existentes en las pymes del sector eléctrico industrial de la ciudad de Cartagena (2020)
Through a descriptive research, a partial diagnosis of the needs and strengths in the metrological management existing in pymes in the industrial electricity sector of the city of Cartagena was achieved.